PENGARUH PROFITABILITAS, LEVERAGE DAN KOMPENSASI RUGI FISKAL TERHADAP TAX AVOIDANCE - Garin Pratiwi Solihati (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2021)
This study aims to determine empirically the effect of profitability, leverage, and tax loss compensation on tax avoidance. Tax avoidance is the dependent variable in this study and the independent variables studied are profitability, leverage and tax loss compensation. This study uses mining companies listed on the Indonesia Stock Exchange in the 2016 - 2018 period as research samples. The research method used was purposive sampling. The object of research is the financial statements of mining companies listed on the Indonesia Stock Exchange in the 2016 - 2018 period. The data is processed by using descriptive statistical tests, classical assumption tests, model suitability tests, and multiple linear regression tests. The results of this study indicate that profitability has an effect on tax avoidance, while leverage and tax loss compensation have no effect on tax avoidance. Keywords: Tax Avoidance, Profitability, Leverage, Fiscal Loss Compensation.